Systematic Literature Review of Gender Bias within Video Games Character Design - Ibrahim, Najwa Sabirah; Senan, Norhalina; Othman, Muhammad Fakri; Azmi, Shahdatunnaim; Erianda, Aldo; Gusman, Taufik (JOIV : International Journal on Informatics Visualization, 2025)
Gender bias in video games refers to the unequal treatment and discrimination that players experience based on gender, which is often normalized within the gaming community. Gender bias is widespread in Multiplayer Online Battle Arena (MOBA) games, where it can take many different forms. Common examples include assumptions made about players' abilities, character design in games, and the roles given to characters according to gender. This situation has created an unwelcoming environment, especially for female players, leading to feelings of exclusion. This study conducts a systematic literature review to examine gender bias in MOBA games, explicitly focusing on character representation, hypersexualized character models, and gameplay mechanics. By analyzing data from peer-reviewed articles, theses, and research papers, the study highlights the recurring patterns of bias and identifies gaps in current approaches. Although prior studies have explored the elements that contribute to gender bias, few studies have offered practical solutions to mitigate this bias. However, there is still a lack of research proposing a practical game design framework that integrates strategies to reduce this bias. In conclusion, efforts to address gender bias are not only significant in terms of design ethics, but also a good strategy in expanding the game's audience. This study identifies possible solutions that might help future research and be developed into a conceptual framework model that developers can understand to create a more inclusive, fair, and profitable gaming environment in the long term.